2019
DOI: 10.2217/fmb-2019-0227
|View full text |Cite
|
Sign up to set email alerts
|

Combating Resistance While Maintaining Innovation: The Future of Antimicrobial Stewardship

Abstract: Antimicrobial resistance represents a significant global health threat. However, a commercial model that does not offer a return on investment resulting in a lack of investment in antibiotic R&D, means that the current pipeline of antibiotics lacks sufficient innovation to meet this challenge. Those responsible for defining, promoting and monitoring the rationale use of antibiotics (the antimicrobial stewardship programme) are key to addressing current shortcomings. In this personal perspective, we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 78 publications
0
9
0
1
Order By: Relevance
“…This is a particular problem in Japan, where only 6 antibiotic agents have been approved since 2002. Conversely, within the same time-frame, the amount of antibiotic agents approved in the United States and the European Union has almost quadrupled this amount, 5 an indication that the development situation of antimicrobial agents in Japan is not as great as in the United States and the European Union.…”
Section: Journal Of Health Economics and Outcomes Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a particular problem in Japan, where only 6 antibiotic agents have been approved since 2002. Conversely, within the same time-frame, the amount of antibiotic agents approved in the United States and the European Union has almost quadrupled this amount, 5 an indication that the development situation of antimicrobial agents in Japan is not as great as in the United States and the European Union.…”
Section: Journal Of Health Economics and Outcomes Researchmentioning
confidence: 99%
“…Increasing AMR means that treatment options for multi-drug resistant bacterial infections are decreasing. Furthermore, the stagnant development of antimicrobial agents is a global problem 1 and the number of antimicrobial agents developed in Japan is even lower than in the European Union and the United States, 5 highlighting the need for appropriate antimicrobial stewardship practices (ASPs) in Japan. 5 Furthermore, despite ample availability of anti-Grampositive agents, including anti-methicillin-resistant Staphylococcus aureus and anti-Vancomycin-resistant Enterococci agents, there is a lack of agents against Gram-negative bacteria and carbapenem-resistant Enterobacterales remains a threat.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that ESBL-producing E. coli isolates from both calf and cow specimens were predominantly inhibited by imipenem and amoxicillin/ clavulanic acid. However, stewardship efforts of preserving the imipenem are a prerequisite [33]. All ESBLproducing E. coli isolates showed a high rate of resistance against β-lactam antimicrobials, oxytetracycline, sulfamethoxazole/trimethoprim, and streptomycin.…”
Section: Antimicrobial Resistance Patternmentioning
confidence: 99%
“…• The highest scoring piece was a special report entitled 'Poliopolis: pushing boundaries of scientific innovations for disease eradication' [5] which was in the top 5% of all research outputs scored by Altmetric. This piece was picked up by 13 news outlets; • A perspective entitled 'Combating resistance while maintaining innovation: the future of antimicrobial stewardship' [6] was at second and in the top 5% of all research outputs scored by Altmetric; • Finally, the editorial article 'Pathogen-associated acute encephalitis syndrome: therapeutics and management' came third [7].…”
Section: Top Altmetric Articlesmentioning
confidence: 99%